Peningkatan Kemampuan Bercerita Pendek Dengan Pemanfaatan Alat Peraga Flip Chart SDN Kedumulyo 02 Sukolilo Pati Tahun 2014-2015 - Ernawati, Tri, Drs. Saring Marsudi, SH. M.Pd (2017)
The purpose of research is to improve student's ability to take advantage of short story-telling props Flip Chart. Type of research is a classroom action research with three cycles of activity. Every cycle consisting of planning, implementation of the action, observation and evaluation, and reflection. As the subject of this research is the teachers and students in grade IV SDN Kedumulyo 02 Sukolilo Pati, which amount to 30 students. Methods of collection of short story-telling abilities through observation and test. Results of study showed that the percentage of short story-telling ability increases, namely : 1) Have a working vocabulary, adjective, adverb, question words, and conjunction. From 18 students (60%), cycle I increased to 22 students (73,33%) and for cycle II increased 28 students (93,33%). 2) Communication skill is 15 students (50%) for cycle I increased to 20 students (66,67%) and cycle II increased 28 students (93,33%). 3) Ability to express thoughts, feelings and actions by using simple sentences is 15 students (50%), for cycle I increased to 20 students (66,67%) and cycle II increased 29 students (96,67%). 4) Able to read and express something through the picture as much as 15 students (50%), for cycle I increased to 20 students (66,67%) and cycle II increased 29 (96,67%). Conclusions of research with the use props Flip Chart can improve the ability to short story-telling in grade IV SDN Kedumulyo 02 Sukolilo Pati.